2006
DOI: 10.1128/iai.74.1.248-256.2006
|View full text |Cite
|
Sign up to set email alerts
|

Implications for Induction of Autoimmunity via Activation of B-1 Cells byHelicobacter pyloriUrease

Abstract: Besides various gastroduodenal diseases,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 42 publications
1
69
0
2
Order By: Relevance
“…In the most recent study, it was concluded that there is generally a negative relationship of various infectious agents, including H. Pylori, in the development of SLE [11]. In an animal study, H. Pylori exposed to urease enzyme was found to lead to the formation of anti-ssDNA antibodies [12]. Generally, the existing evidence does not support that H. Pylori has a role in the development of SLE [13].…”
Section: H Pylorı and Slementioning
confidence: 98%
“…In the most recent study, it was concluded that there is generally a negative relationship of various infectious agents, including H. Pylori, in the development of SLE [11]. In an animal study, H. Pylori exposed to urease enzyme was found to lead to the formation of anti-ssDNA antibodies [12]. Generally, the existing evidence does not support that H. Pylori has a role in the development of SLE [13].…”
Section: H Pylorı and Slementioning
confidence: 98%
“…This hypothesis may explain the observed variability in treatment effect by country since CagA-positive strains of H. pylori are more prevalent in Japan than in North America. 28 Other proposed mechanisms are modulation of host immunity following colonization by H. pylori to favor the emergence of autoreactive B-1 cells 29 and the enhancement of phagocytic capacity of monocytes together with low levels of the inhibitory Fcγ receptor IIB following H. pylori infection. 30 Our findings raise questions that merit further research.…”
Section: Discussionmentioning
confidence: 99%
“…In an animal study, it was found that exposure to H.pylori urease can lead to production of anti-single stranded DNA antibodies [39]. Kalabay and colleagues studied the prevalence of anti-H.pylori antibodies in various autoimmune rheumatic diseases and they found the comparable prevalence of H.pylori in SLE patients and healthy controls [40].…”
Section: Discussionmentioning
confidence: 99%